JUMLAH DANA ZAKAT DAN FAKTOR-FAKTOR MAKROEKONOMI YANG MEMPENGARUHINYA - Kiki Novitasari; Suherman Rosyidi (Universitas Airlangga, 2018)
The aim of this study was to know the impact of macroeconomic indicators changes toward the total amount of collected zakah in BAZNAS during the period 2012-2016. This study uses qualitative approach by using liniear regression analysis technique. Futhermore dependent variable used in this study is the amount of zakah, while the independent variable are inflation, gold price, money supply and industrial production index. The determination of sampling uses non probability sampling with saturated sample method, on the other hand, the whole population was used as the sample of this study. Moreover, the data used in this study is secondary data. REFERENCESAnshori, Muslich dan Sri Iswati. 2009. Buku Ajar Metodologi Peneliti Kuantitatif. Surabaya: Airlangga University Press.Ahmad, Zulfikar Muzakir. 2011. Pengaruh Indikator Makroekonomi Terhadap Besarnya Jumlah Zakat Yang Terkumpul di Lembaga Amil Zakat Dompet Dhuafa Republika Tahun 1993-2009. Tesis tidak diterbitkan. Jakarta. Universitas IndonesiaAl-Zuhayly, Wahbah. 2008. Zakat: Kajian Berbagai Mazhab. Bandung: Remaja Rosdakarya.Boediono, 1982. Ekonomi Makro Edisi 4. BPFE-UGM: Yogyakarta.BAZNAS, 20013. Outlook Zakat 2014. JakartaBAZNAS, 20016. Outlook Zakat 2017. JakartaChapra, Umer. 2000. Sistem Moneter Islam. Jakarta: Gema Insani Press.Dwitama, Rio Budi. 2015. Pengaruh Nilai Tukar Rupiah Dan Inflasi Terhadap Jumlah Dana Zakat Di Lembaga Amil Zakat Dompet Dhuafa Periode 1997-2003. Surabaya: Universitas Airlangga Fahme, Ahmad, et al. 2015. The Effectiveness of Zakat in Reducing Poverty Incident: An Analysis in Kelantan. Malaysia. Asian Social Science. Vol.11, No.21 Fatma, Fahma Sari. 2005. Pengaruh Inflasi dan Pengangguran terhadapKemiskinan di Indonesia. Tesis tidak diterbitkan. Jakarta: UniversitasIndonesiaGujarati, Damodar N. 2004. Basic Econometrics (edisi keempat). The McGrawHill Companies.Huda, Nurul dkk. 2008. Ekonomi Makro Islam: Pendekatan Teoritis. Jakarta:Prenada Media Grup.Hafidhuddin, Didin. 2002. Zakat dalam Perekonomian Modern. Jakarta: GemaInsani.Hakim, Abdul. 2001. Statistik Deskriptif untuk Ekonomi dan Bisnis. Yogyakarta: Ekonosia.Karim, Adiwarman A. 2015. Ekonomi Makro Islami. Jakarta: Rajawali Pers.Kameel, Ahmad, et al. 2009. Seigniorage of Fiat Money and The Maqasid Al-Shari’ah: The Compatibility of The Gold Dinar with The Maqasid. Jurnal Muamalat Bil. Vol.2Kementerian Agama RI. 2014. Al-Qur’an dan Terjemahan untuk Wanita. Penerbit WALI: Oasis Terrace Recident. Jakarta.Majdi, Hafiz. 2010. Motivation of Paying Zakat On Income: Evidence fromMalaysia. International Journal of Economics and Finance, 2 (3): 76-84Nachrowi, D. 2006. Ekonometrika, untuk Analisis Ekonomi dan Keuangan. Jakarta: Lembaga Penerbit FE UI.Naf’an, 2014. Ekonomi Makro; Tinjauan Ekonomi Syariah. Yogyakarta: Graha Ilmu.Noviyanti. 2016. Pengaruh Variabel Makro Terhadap Penerimaan ZIS Dompet Dhuafa. Bogor. Intitut Pertanian Bogor.Rahardjo, Prathama dan Mandala Manurung. 2001. Teori Ekonomi Makro. Penerbit Fakultas Ekonomi Universitas Indonesia.Republik Indonesia. 2011. Undang-Undang No.23 Tahun 2011 tentang Pengelolaan Zakat. Lembaran Negara RI Tahun 2011, No. 115. Sekretaria NegaraRosyidi, Suherman. 2017. Pengantar Teori Ekonomi: Pendekatan Kepada Teori Ekonomi Mikro dan Makro. Jakarta: Rajawali Pers.Sanusi, Mahmood. 2001. Gold Dinar, Paper Currency and Monetary Stability: An Islamic View. IIUM Law Journal. Vol.9, No.2Singgih, Ovina. 2016. Pengaruh Harga Minyak Dunia terhadap Pertumbuhan Output, Indeks Produksi Industri, Indeks Harga Konsumen, Nilai Tukar dan Suku Bunga di Indonesia. Surabaya: Universitas AirlanggaSukirno, Sadono, 1981, Pengantar Teori Makro Ekonomi, Jakarta; Bina Grafika. ——–. 2004. Makroekonomi Teori Pengantar Edisi Ketiga. PT RajaGrafindoPersada: Jakarta.Soesastro, Hadi dkk. 2005. Pemikiran dan Permasalahan Ekonomi di Indonesia dalam Setengah Abad Terakhir. Yogyakarta: Kanisius.Widarjono, Agus. 2010. Analisis Statistika Multivariant Terapan. Yogyakarta: UPP STIM YKPN.Zaiton, Nurshuhaida. 2013. Implementation Gold Dinar: Is It Feasible?. Prosiding Perkem VIII, Jilid 3http://dsnmui.or.idhttp://bi.go.id http://bps.go.id http://pusat.baznas.go.idwww.harga-emas.com